E.T.A. Hoffmann's Other World : the Romantic Author and His "New Mythology" - Negus, Kenneth (University of Pennsylvania Studies in Germanic Languages and Literatures, 2016)
In this study of the imaginary universe of Germany's most famous author of fantasy, Kenneth Negus attempts to establish the coherency and fathom the depth of the "other world" manifested in Hoffmann's many tales.Proceeding mainly from Der Goldene Topf, Hoffmann's most fully developed mystical work, Negus shows how the figures, themes, and motifs Hoffmann established permeate his tales, forming a basic overall structure that embodies creation, destruction, and the interaction of the two extremes in a mythology that is a fantastic distillation of the real world with which it is often in conflict.This close and careful scrutiny of the work of E. T. A. Hoffmann should be of major interest to all teachers and students of German and Comparative Literature.